Maturation of the Pupil Light Reflex Occurs Until Adulthood in Mice - Kircher, Noémie; Crippa, Sylvain V.; Martin, Catherine; Kawasaki, Aki; Kostic, Corinne (Frontiers in Neurology, 2019)
This study examines the maturation of pupil light response (PLR) and retinal activity in C57BL/6 and Sv129S6 wild-type mice. It is well known that electroretinography (ERG) decreases with age, but to our knowledge, studies showing age-related changes in mouse PLR are missing. Dark-adapted PLR and ERG were performed at 1, 2 and 4 months of age. For the PLR, a single monocular light stimulus (500 ms) was applied, either red (622  8 nm) or blue (463  8 nm) with a range of intensities over almost 4 log units (low, medium, high). Baseline pupil size (mean pupil diameter before the light stimulus), maximal constriction amplitude (change from baseline during the first 1.8 seconds following stimulus onset), maximal velocity (during the first 1.8 seconds following stimulus onset), early partial dilation (area under the curve of the positive peak of the PLR tracing’s 1st derivative), sustained response (constriction amplitude at 9.5 seconds following stimulus offset) and ratio (sustained amplitude to maximal constriction amplitude) were the tested parameters. For ERG, both scotopic and photopic responses were recorded, then amplitudes and latencies of a-wave and b-wave were determined. A smaller baseline pupil diameter was noted in 1 month-old animals compared to 2 and 4 month-old mice. One month-old mice showed increased maximal contraction amplitude only in response to medium red stimuli compared to the 2 and 4 month-old animals. The one month-old mouse PLR differed also from the results at 2 and 4 months with a faster early partial dilation in response to low blue stimuli and a decreased sustained response at 9.5 seconds. These results suggest that the functional maturation of the PLR pathway take places after 1 month of age and that the normative values for mouse PLR should be performed from 2 months of age.